Documenting Butterflies Diversity (Lepidoptera: Rhopalocera: Nymphalidae) as Potential Nature Tourism Products at Sukau Rainforest Lodge and Sukau Ecotourism Research Centre, Kinabatangan, Sabah - Mohammad Amil Zulhilmi Benjamin; Mahadimenakbar Mohamed Dawood; Nazirah Mustaffa; Homathevi Rahman; Fiffy Hanisdah Saikim (Universiti Malaysia Sabah, 2021)
Sukau Rainforest Lodge (SRL) and Sukau Ecotourism Research Centre (SERC) have been recognized as two ecotourism sites in Sabah. However, there were no butterfly tourism products carried out at both sites. As a result, a 5-day survey of butterfly diversity was conducted using fruit-baited traps. Butterfly diversity, richness, and abundance were evaluated using Shannon-Weiner Diversity for both sites. SWOT analysis was also carried out at both sites throughout a 3-week observation. The results showed there were 20 species from 6 subfamilies of Nymphalidae butterflies. A total of 96 individuals of each species were also tabulated, with SRL revealing a higher diversity index compared to SERC due to its large surrounding area. The butterfly specimens were collected for educational purposes as nature tourism products. Lack of research, no butterfly signage, forest fragmentation, and mass tourism activities were identified as weaknesses and threats with their strengths and opportunities as proper guidelines based on SWOT analysis. Hence, it shows that both sites are valuable for nature tourism based on their unique butterfly fauna as butterfly tourism products. This study could also provide baseline data on butterfly diversity and its potential as butterfly tourism products at both sites. Butterfly diversity data and SWOT analysis are compulsory for the creation of butterfly tourism products. Such valuable fauna can be integrated as nature tourism products in conjunction with appropriate decision-making strategies.